Application of Truth Criterion for Isolated Utterances - Meškauskas, Eugenijus (Problemos, 1983)
In the paper an attempt is made to prove that an independent unit for comparing the results of cognition process with reality should be considered the one that explains its theory as a whole. Isolated utterances do not count, as their real sense depends on the content of the theory which they are related to. The question on the truth of utterances ascertaining facts of everyday occurrence is not a gnoseological problem.